The Connection between coping mechanisms, depression, anxiety and fatigue in multiple sclerosis - Brajković, Lovorka (Array, 2009)
Summary: The aim of this study was to show how different coping mechanisms influence the prevalence of anxiety and depression in people suffering from multiple sclerosis. We also aimed at showing how different coping mechanisms contribute to subjective prosperity of the patients emphasizing general health, cognitive functions and fatigue. A questionnaire was given to attendants of the VI Symposium of Patients Suffering From Multiple Sclerosis. Scales were taken from Multiple Sclerosis Quality of Life Inventory (MSQLI), Hospital Anxiety and Depression Scale (HADS) and COPE inventory. A total of 68 anonymous questionnaires were handed in. A total of 57.9% of examinees had symptoms of depression, and 63.2% suffered from symptoms of anxiety. However, majority of the examinees suffered from the combination of these entities. Hypothesis about impact of various coping factors on depression, anxiety, fatigue was validated except an impact on physical state was not proven significant. Predictors improving these states were positive reinterpretation, social emotional support and humor, Predictors worsening these states were planning, acceptance, focus on emotional ventilation and denial. Psychiatric comorbidity has a high prevalence in people suffering from MS. Different coping mechanisms can help in improvement of everyday life